Troponin I, CK-MB, and inotropic score in hypoxic-ischemic encephalopathy and associated infant mortality - Hayriye Gözde Kanmaz Kutman; Gülsüm Kadıoğlu Şimşek; Burak Ceran; Esra Beşer; Fuat Emre Canpolat (BMC, 2023)
Abstract Purpose Cardiovascular dysfunction is common in hypoxic-ischemic encephalopathy (HIE), which is one of the leading causes of multi-organ failure in neonates. We aimed to assess troponin I and creatine kinase myocardial band (CK-MB) levels, inotropic score (IS) in HIE patients, and their associations with HIE staging and mortality. Method The medical records of all HIE infants admitted to our unit between 2016 and 2018 were retrospectively analyzed. Demographic characteristics of the infants, seizures, anticonvulsive therapies, maximum inotrope doses, and the derived IS (dopamine dose [µg/kg/min] + dobutamine dose [µg/kg/min] + 100 × epinephrine dose [µg/kg/min]) and CK-MB and troponin-I levels obtained in the first six hours of life were compared according to HIE staging. Comparisons between survivors and non-survivors were made. Results The study included data from 195 patients. Twenty-five patients were classified as stage 3, 116 as stage 2, and 54 as stage 1 HIE. Median Troponin-I, CK-MB level, and IS significantly differed by HIE staging (p < 0.01). The deceased infants had significantly higher median troponin I level [0.36 (0.02-3) vs. 0.16 (0.01-1.1) ng/ml; p = 0.006], median IS [20 (5-120) vs. 5 (5-10); p < 0.001], however, CK-MB values were comparable with survivors [129 (51-300) vs. 60.7 (31-300) ng/ml; p = 0.57]. The area under the curve was 0.93 for IS and 0.81 for Troponin I to predict mortality. Conclusion Troponin I, CK-MB, and IS could be successfully used as disease severity markers in HIE furthermore, troponin I and IS, are good predictors of mortality. These results need to be confirmed with larger prospective multi-center studies.